Effect of Irrigation Using Diluted Winery Wastewater on the Chemical Status of a Sandy Alluvial Soil, With Particular Reference to Potassium and Sodium - Howell, C.L.; Myburgh, P.A.; Lategan, E.L.; Hoffman, J.E. (South African Journal of Enology and Viticulture, 2018)
The re-use of winery wastewater for irrigation was investigated in a field trial with micro-sprinklerirrigated Cabernet Sauvignon/99 Richter in the Breede River Valley region of South Africa. Irrigation with winery wastewater diluted with river water to 100, 250, 500, 1 000, 1 500, 2 000, 2 500 and 3 000 mg/L chemical oxygen demand (COD) was compared to irrigation with river water. No trends were found in soil pH(KCl) and electrical conductivity of the saturated soil extract (ECe ) that were related to the different levels of dilution. However, ECe was considerably higher after the application of diluted winery wastewater irrigations compared to ECe at bud break. This suggests an accumulation of salts from the diluted winery wastewater. Under the prevailing conditions, soil K+ and Na+ increased with a decrease in the dilution of the winery wastewater. Increases in K+ could have a negative impact on wine colour stability should potassium be taken up by the grapevine in sufficient quantities, particularly if soil K+ accumulates to such an extent that it is luxuriously absorbed by grapevines. There were no consistent trends with regard to soil organic C, which indicates that there was too little organic material in the wastewater to have had a positive effect on soil fertility. Furthermore, organic material in the wastewater probably oxidised when the soil was aerated between irrigations. Although irrigation with diluted winery wastewater had almost no other effects, element accumulation, particularly with respect to K+ and Na+, might be more prominent in heavier soils or in regions with low winter rainfall.